Metabolism of sulfur compounds by whole filaments and heterocysts of Anabaena variabilis. - Giddings, T H (1981)
Filaments of the heterocyst-forming cyanobacterium Anabaena variabilis reproduced 35SO4(2)-, incorporating 35S into cysteine, methionine, glutathione, sulfolipid, and several unidentified metabolites. The majority of the incorporated label accumulated in reduced glutathione. Heterocysts isolated from labeled filaments contained the same major labeled products. Isolated, metabolically active heterocysts were unable to reduce 35SO4(2)-, but were able to incorporate 35S2- into cysteine and glutathione. The results suggest that the initial activation of SO4(2)- occurs in vegetative cells and that some reduced forms, possibly including S20, are translocated into heterocysts.